2013
DOI: 10.1063/1.4821024
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ferromagnetic moment in Co-doped BiFeO3 thin films studied by soft x-ray circular dichroism

Abstract: BiFeO3 (BFO) shows both ferroelectricity and magnetic ordering at room temperature but its ferromagnetic component, which is due to spin canting, is negligible. Substitution of transitionmetal atoms such as Co for Fe is known to enhance the ferromagnetic component in BFO. In order to reveal the origin of such magnetization enhancement, we performed soft x-ray absorption spectroscopy (XAS) and soft x-ray magnetic circular dichroism (XMCD) studies of BiFe1−xCoxO3 (x = 0 to 0.30) (BFCO) thin films grown on LaAlO3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…In Fig. 2(a) one can see that after having subtracted the FePt XAS spectrum multiplied by ∼0.5, the spectral line shape became similar to that of BiFeO 3 , where the Fe 3+ ion is located at the O h site [23], shown in the bottom of Fig. 2(a).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In Fig. 2(a) one can see that after having subtracted the FePt XAS spectrum multiplied by ∼0.5, the spectral line shape became similar to that of BiFeO 3 , where the Fe 3+ ion is located at the O h site [23], shown in the bottom of Fig. 2(a).…”
mentioning
confidence: 85%
“…[8], dotted curve) are shown at the top. The XMCD spectrum of BiFeO 3 by Singh et al [23] is shown at the bottom.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By applying the sum rules [1,2,20,[25][26][27][28][29][30][31], we obtained the spin and orbital magnetic moments of the Mn atom from the XAS and XMCD spectra. We assumed the contribution of the dipole operator term T z in the spin sum rule to be negligibly small because the Mn atom in CMS is located at the high-symmetry T d site [2].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the Co magnetic moment, we applied the sum rules [1,2,20,[25][26][27][28][29][30][31] as in the case of the Mn L 3,2 -edges. Since the Co atoms are also in the highlysymmetry T d crystal field, we again neglect the T z term in the spin sum rule [2].…”
Section: Resultsmentioning
confidence: 99%